2018
DOI: 10.1007/s00011-018-1136-9
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin H deficiency in mice induces excess Th1 cell activation and early-onset of EAE though impairment of toll-like receptor 3 cascade

Abstract: CatH showed a significantly earlier disease onset of EAE and increased Th1 cell differentiation in splenocytes. Splenocytes prepared from immunized CatH showed a significant decrease in poly(I:C)-induced increased TLR3 expression, interferon regulatory factor 3 (IRF3) phospholylation and IFN-β secretion. Therefore, CatH deficiency impaired TLR3-mediated activation of IRF3 and consequent secretion of IFN-β from dendritic cells, leading to the enhancement of Th1 cell differentiation and consequent early disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…Although we speculated that CatH might have the same functions as CatB in the HI model, the present study has revealed their differential pathological roles. Our previous [11] and the present studies suggest that CatH is necessary for the activation of TLR3/IRF3 signaling and consequent secretion of IFN-β through proteolytic maturation and stabilization of TLR3. It is noted that TLR4 and TLR3 are differentially involved in the cerebral HI damage.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Although we speculated that CatH might have the same functions as CatB in the HI model, the present study has revealed their differential pathological roles. Our previous [11] and the present studies suggest that CatH is necessary for the activation of TLR3/IRF3 signaling and consequent secretion of IFN-β through proteolytic maturation and stabilization of TLR3. It is noted that TLR4 and TLR3 are differentially involved in the cerebral HI damage.…”
Section: Discussionsupporting
confidence: 71%
“…CatH (EC 3.4.22.16) is a lysosomal cysteine protease with a unique aminopeptidase activity, and its expression level is increased in activated immune cells [ 10 , 11 ]. Recently, we have reported that CatH deficiency impaired toll-like receptor 3 (TLR3)-mediated activation of interferon regulatory factor 3 (IRF3) and consequent secretion of interferon-β (IFN-β) from dendritic cells [ 11 ]. Furthermore, there is increasing evidence that IFN-β secreted from microglia/macrophages has neuroprotective effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTSH encodes cathepsin H, which is a member of the papain-like cysteine proteases that are primarily involved in endolysosomal protein degradation, activation of other proteases ( 21 ), as well as major histocompatibility complex class II antigen presentation. Although CTSH -null mice do not demonstrate gross developmental defects ( 22 ), CTSH was associated with autoimmunity in mouse models and humans including experimental autoimmune encephalomyelitis ( 23 ) and T1D ( 24 ). CTSH is expressed in pancreatic beta cells and antigen-presenting cells but not in T cells ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…TLR3/MyD88 independent pathway promotes the secretion of IL-27 to suppress the mature of Th17 cells ( 69 ). The lack of Cathepsin H damages TLR3-mediated IRF3 activation, inhibits IFN-β secretion from DCs and promotes Th1 cell differentiation ( 70 ). Activation of TLR3 in astrocytes induces the expression of neuroprotective mediators, including anti-inflammatory cytokines IL-9, IL-10, and IL-11, and down-regulates the secretion of pro-inflammatory cytokines IL-12 and IL-23, and inhibits gliosis and promotes neuronal survival, angiogenesis, and myelin regeneration ( 71 , 72 ).…”
Section: Role Of Tlrs In Neuroimmune Diseasesmentioning
confidence: 99%